PENGARUH INFORMASI GOODWILL PADA RELEVANSI HUBUNGAN ANTARA LAPORAN KEUANGAN DAN RETURN SAHAM - Yenni Karina (Jurnal Riset Akuntansi dan Keuangan, 2006)
goodwill informdion to vdue relev**e baweenfu,odal stdement and stock ?etrrn. This reseqrhws done kcare in a rcst Australia sndy, Jones (2M3) faurd thd tle cryitalim*m 6 i,rtmgibles is significantly higher in tlp neat ecoreomy sector od b*angible rcsets represented a significant proportion of total assets il, this seeton Tltk study ases manutac' twing firms listed in tlu Jak&ta 9*k Exclwrge (BEI) wilhin 1990 - 20A3. The results ou b@y brqaistart with tIre Australia sady. 71te result of eramination shows tM ttv valw televotce between annual clunge in earnings, qnual chorye in cosh fiow ftom operations, or' nual rcported accruals ond stoc* retwn was significantly higher withthe discloswe of goadwiil intonwtim h $rrorcial statemeat. And thevahrc rclevstce between e@rrirr& wrtfrffifrorn operdiotts, tle clrange in o*ual reported rccnuls and stod..rwa*as tnt signifrcottly higler with the discloswe of godviW ir@i@, b fwrcisl statenwnt.Keyword: value rclevotce, e*nings, @nr.ot chorye in eunings, cashJlow from operations, omual change in cash tlow fromoperations, annusl reported accntals, the change in annualreported acentals, goodwill